2007
DOI: 10.1177/09612033070160040901
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine increases low-density lipoprotein removal from plasma in systemic lupus patients

Abstract: Low-density lipoprotein (LDL) pathway in systemic lupus erythematosus (SLE) patients taking chloroquine diphosphate (CDP) was evaluated through the kinetic behavior of a radioactive cholesterol-rich nanoemulsion (LDE) that resembles the LDL lipidic structure. LDE was labeled with (14)C-cholesteryl ester ((14)C-CE), then IV injected in inactive female SLE patients: 10 taking CDP (CDP), 10 without therapy (NO THERAPY); and 10 normal subjects (CONTROL). Groups were age-matched and followed rigorous selection crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 64 publications
(73 reference statements)
2
46
0
4
Order By: Relevance
“…This was noted particularly in patients on steroid treatment, where antimalarial drugs lowered TG and very LDL (VLDL) in one of these studies [7] and in another study total cholesterol, VLDL and LDL levels were lower in SLE patients on the similar medical regimen [8]. Furthermore, LDL uptake from plasma is increased in SLE patients on steroids and antimalarial drugs compared with steroid-treated SLE patients, without antimalarial drugs [9].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This was noted particularly in patients on steroid treatment, where antimalarial drugs lowered TG and very LDL (VLDL) in one of these studies [7] and in another study total cholesterol, VLDL and LDL levels were lower in SLE patients on the similar medical regimen [8]. Furthermore, LDL uptake from plasma is increased in SLE patients on steroids and antimalarial drugs compared with steroid-treated SLE patients, without antimalarial drugs [9].…”
Section: Discussionmentioning
confidence: 98%
“…Traditional risk factors as well as SLE-specific risk factors have been thoroughly studied and both are of importance for the development of cardiovascular disease in SLE [4][5][6]. It has been suggested that antimalarial (hydroxychloroquine and chloroquine diphosphate) treatment might improve the blood lipid profile in SLE and reduce the risk of diabetes mellitus [7][8][9][10][11].There is a clinical need for non-invasive techniques to ensure the presence of and predict the development of cardiovascular disease in SLE. Non-invasive methods have been used to investigate vessel wall changes, and revealed increased vessel wall stiffness and increased pulse wave velocity in SLE patients compared with controls [12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 six case-control studies [38][39][40][41][42][43] ) examining the effects of HCQ on LDL as shown in Figure 2a. Heterogeneity was extensive (I 2 = 94.739%).…”
Section: Effect Of Hcq On Serum Ldlmentioning
confidence: 99%
“…There is no consistent data regarding whether this antithrombotic effect is present both for arterial and venous events. A beneficial effect on serum lipid levels, including patients taking corticosteroid therapy (Borba et al, 2001;Hodis et al, 1993;Sachet et al, 2007;Tam et al, 2000), was shown by a few observational studies. However, the strenght of evidence supporting a clinically meaningful beneficial effect was rated as low.…”
Section: Hydroxychloroquinementioning
confidence: 99%